Dielectric And Magnetic Characterization Of (La0.5-Xprxba0.5)(Mn0.5ti0.5)O3 Perovskite As A Multiferroic Material Synthesized Via Solid State Technique - Alias, Nor Hayati (2009)

(untitled)
A new manganate perovskite (La0.5-xPrxBa0.5)(Mn0.5Ti0.5)O3 has been prepared by ceramic solid-state technique at sintering temperature 1300 °C for 24 hours. The x concentration of Praseodymiun (Pr) in molar proportion in A site has been varied as x = 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 007, 0.08, 0.09, 0.1, 0.2, 0.3 and 0.4. The dielectric properties of the synthesized materials have been studied at frequency ranging from 5 Hz to 1 MHz from room temperature up to 200 °C. Furthermore, analyses have been carried out to determine the structural, magnetic and dielectric electrical properties of the synthesized material as a candidate of multiferroic material. Pr (Praseodymium) addition would promote liquid phase sintering in the synthesized samples. This enhanced the agglomeration and porosity formation in the bulk volume. The defects and conducting liquid present would generate traps that produce negative permittivity response at interfacial/space charge frequency region due to delay in transient current or situation in which inertial conducting current of the trap presents, exceeding the charging-discharging current component. The XRD (X-Ray Diffractometry) results indicate all samples possess a single phase monoclinic structure with space group P112. Multiferroic magnetodielectric coupling in material with ferromagnetic and high dielectric constant ( > 30) is able to achieve in sampel with x molar concentration = 0.07 at room temperature. The dielectric value obtained is 176 with loss tan δ value 0.62. SEM/EDX analysis of the sample shows fine grain microstructure and high manganese (Mn) content ( > 0.6 wt